2020
DOI: 10.1101/2020.06.03.132662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local adaptation can cause both peaks and troughs in nucleotide diversity within populations

Abstract: Local adaptation is expected to cause high FST at sites linked to a causal locus, however this pattern can also be driven by background or positive selection. Within-population nucleotide diversity could provide a means to differentiate these scenarios, as both background and positive selection deplete diversity, whereas some theoretical studies have shown that local adaptation increases it. However, it is unclear whether such theoretical predictions generalize to more complicated models. Here, we explore how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Overall, our demographic model suggests that migration between marine and freshwater populations is common, especially after the build-up of the Lake Washington Ship Canal. This is consistent with a scenario of gene flow increasing diversity near regions under selection ( Jasper and Yeaman 2020 ) and our result that regions with high genetic diversity are associated with regions under selection. Similar results have been observed in Alaskan populations of G. aculeatus , with low genetic diversity in marine populations and high genetic diversity in freshwater populations in regions of the genome under divergent selection ( Nelson et al 2019 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our demographic model suggests that migration between marine and freshwater populations is common, especially after the build-up of the Lake Washington Ship Canal. This is consistent with a scenario of gene flow increasing diversity near regions under selection ( Jasper and Yeaman 2020 ) and our result that regions with high genetic diversity are associated with regions under selection. Similar results have been observed in Alaskan populations of G. aculeatus , with low genetic diversity in marine populations and high genetic diversity in freshwater populations in regions of the genome under divergent selection ( Nelson et al 2019 ).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, freshwater populations are expected to have a smaller population size, where genetic drift would have a more powerful influence, leading to a faster loss of genetic diversity in the freshwater population. However, a recent simulation study has pointed out that gene flow can not only homogenize the genome but also increase diversity near regions under selection ( Jasper and Yeaman 2020 ). To determine whether gene flow can explain the distribution of nucleotide diversity in our data, we built several demographic models ( supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…We did not attempt to disentangle these competing theories due to the characteristics of Rapture data (i.e., a low percentage of the genome is sampled compared to whole genome sequencing and extracting invariant sites is difficult). In addition, a recent simulation study has demonstrated that there is no universally diagnostic signature of local adaptation based on nucleotide diversity within populations, which can be decreased or increased depending on the relative strengths of migration and selection (Jasper & Yeaman, 2020 ), further complicating this debate. Other factors such as variation in recombination, mutation rate, and gene density can also lead to a heterogeneous genomic landscape of differentiation (Ravinet et al, 2017 ; Schumer et al, 2018 ), but exploring these is beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, conditionally beneficial alleles or recently established spatially antagonistic ones would resemble the “lag” type of F ST peak observed under global adaptation, that is, with no increase in d XY . Note that π W is not a particularly useful diagnostic for local adaptation as either increased or decreased levels relative to background can occur depending on the relative strength of migration and selection (Jasper and Yeaman 2020). Taken together, our results suggest that only prolonged periods of local adaptation driven by antagonistic pleiotropy can reliably be distinguished from global adaptation.…”
Section: Ongoing and Recent Selective Sweeps Of Globally Beneficial Mmentioning
confidence: 99%